Performance of Ankleshwar Chicken Reared under Intensive Management System in Gujarat - Patel, AB; Bhagora, NJ; Savaliya, FP; Mishra, RK; Lonkar, VD (Indian Journal of Veterinary Sciences and Biotechnology, 2020)
The productive and reproductive performance of Ankleshwar chicken under intensive management for three successive generations(S0, S1, and S2) was studied at Poultry Research Station, AAU, Anand, Gujarat. Total 546, 422, and 465 pullets of S0, S1, and S2 generation,respectively, were housed in individual layer cages at 16 weeks of age. Production parameters, viz., body weight (g) of day-old, 4th,8th, 16th and 40th weeks of age; total feed consumption (kg) per bird; mortality (%) during 0-8, 9-16 and 17-40 weeks of age; total eggproduction (no.) up to 40 weeks of age and average egg weight (g) at the end of 28th and 40th week of age were recorded for threegenerations. The reproductive parameters, viz., age at sexual maturity (days), fertility (%) and hatchability (%) on Total Egg Set basis(TES) as well as hatchability on Fertile Egg Set basis (FES) were calculated. It was concluded that the rearing of Ankleshwar chicken inintensive management over three (S0, S1 and S2) generations significantly (p≤0.05) improved body weight at 4th, 8th and 16th weeks ofage, required less feed, improved fertility and showed significantly (p ≤0.05) early age at sexual maturity (154 days) in S2 generationwith significant (p≤0.05) decreasing trend in egg production up to 40th week of age from S0 to S2 generation. Hatchability showed adecreasing trend in progressive generations. The birds have shown better livability reared under intensive management in Gujarat.
Keywords: Ankleshwar chicken; Gujarat climate; Intensive system; Productive performance